A Multiwalled-Carbon-Nanotube-Based Biosensor for Monitoring Microcystin-LR in Sources of Drinking Water Supplies - Han, Changseok; Doepke, Amos; Cho, Wondong; Likodimos, Vlassis; de la Cruz, Armah A.; Back, Tyson; Heineman, William R.; Halsall, H. Brian; Shanov, Vesselin N.; Schulz, Mark J.; Falaras, Polycarpos; Dionysiou, Dionysios D. (Advanced functional materials, 2013)
A multiwalled carbon nanotube (MWCNT)‐based electrochemical biosensor is developed for monitoring microcystin‐LR (MC‐LR), a toxic cyanobacterial toxin, in sources of drinking water supplies. The biosensor electrodes are fabricated using vertically well‐aligned, dense, millimeter‐long MWCNT arrays with a narrow size distribution, grown on patterned Si substrates by water‐assisted chemical vapor deposition. High temperature thermal treatment (2500 °C) in an Ar atmosphere is used to enhance the crystallinity of the pristine materials, followed by electrochemical functionalization in alkaline solution to produce oxygen‐containing functional groups on the MWCNT surface, thus providing the anchoring sites for linking molecules that allow the immobilization of MC‐LR onto the MWCNT array electrodes. Addition of the monoclonal antibodies specific to MC‐LR in the incubation solutions offers the required sensor specificity for toxin detection. The performance of the MWCNT array biosensor is evaluated using micro‐Raman spectroscopy, including polarized Raman measurements, X‐ray photoelectron spectroscopy, cyclic voltammetry, optical microscopy, and Faradaic electrochemical impedance spectroscopy. A linear dependence of the electron‐transfer resistance on the MC‐LR concentration is observed in the range of 0.05 to 20 μg L−1, which enables cyanotoxin monitoring well below the World Health Organization (WHO) provisional concentration limit of 1 μg L−1 for MC‐LR in drinking water. An highly sensitive Faradaic electrochemical impedance biosensor for monitoring microcystin‐LR (MC‐LR) in sources of drinking water supplies is developed using millimeter‐long multiwalled carbon nanotube (MWCNT) arrays grown by water‐assisted chemical vapor deposition with vertical alignment. A linear sensing response shows a wide microcystin‐LR concentration range that is below the World Health Organization (WHO) provisional guideline limit of 1 μg L−1 for MC‐LR in drinking water.